Rural Youth's perception of beekeeping developed in rural communities in the semiarid region of Piauí - Patrícia Sara Lopes Melo; Michelli Ferreira dos Santos; Maurício Fernandes da Silva; Juliana do Nascimento Bendini (Universidade Federal do Norte do Tocantins, 2022)
In the state of Piauí, beekeeping presents itself as an alternative to generate income for peasant families, more precisely in the semiarid region. This study aimed to analyze the perception of young people in relation to beekeeping practiced in the city of Massapê do Piauí. Therefore, a semi-structured questionnaire was applied to 48 students from rural communities. It was observed that young people, in general, do not identify with rural activities, although many have some degree of kinship with beekeepers. Most young people had little knowledge about beekeeping, especially with regard to the prevention of accidents with bees (stinged). It is noteworthy that many of them consider the stings as the biggest obstacle to entering the activity. Although they know the social, economic and environmental importance of beekeeping, as well as the negative impacts that the disappearance of bees would cause in their communities, most young people did not show interest in participating in training to start beekeeping. Given the notable apathy of students in relation to beekeeping, it is suggested actions aimed at knowledge and awareness of youth in relation to the activity as an important tool for social and economic inclusion for agents in the rural community.